Cevap:
Altında
Açıklama:
6. = 7 / x + x # nerede # katı! = 0 #
7. / x = 6-x #
# X, ^ 2 * 7 / x = x ^ 2 (6-x) #
# 7x = 6x ^ 2-x ^ 3 #
# X ^ 3-6x ^ 2 + 7x = 0 #
# x (x ^ 2-6x + 7) = 0 #
#, X = 0 # veya # X ^ 2-6x + 7 = 0 #
İçin # X ^ 2-6x + 7 = 0 #, ikinci dereceden formül kullanmamız gerekiyor
yani # x = (B + - -sqrt (b ^ 2-4ac)) / (2a) #
#, X = (6 + -sqrt (36-28)) / (2) #
#, X = (6 + -2sqrt2) / 2 #
#, X = 3 + -sqrt2 #
AMA bakıyor #, X = 0 #, çünkü bir çözüm olamaz #7/0#
Bu nedenle, cevap #, X = 3 + -sqrt2 #